Philosophical and Religious Sources of Modern Culture (European Studies in Theology, Philosophy and History of Religions, 2012)
Europe is the community of nations which, in the favorable conditions of a small yet extremely diversified continent, took over and developed the legacy of Greco-Roman civilization transformed and enriched by Christianity. Philosophy, theology, liturgy, religion, national culture and tradition are still manifestations of this heritage. Europe is not merely a region or geographical location. It is an idea that expresses cultural and social ideals. The nature of Europeanness is not defined by race or place but by freedom and culture in the broad sense. Latin Europe created a sphere of civilization. Though ridden by contrasts and differences, not merely an organic unity was established but also a unity of a spiritual kind by accentuating and merging of values all Europeans have in common. This was also made possible by Christianity whose ethos came to pervade a multiplicity of socio-cultural phenomena